Uso de habitat e migração norte do Calidris canutus rufa (maçarico-de-papo-vermelho) do extremo sul do Brasil ao Canadá - Brum, Antônio Coimbra de (Universidade do Vale do Rio dos Sinos, 2021)
During migration to breeding or wintering areas, Calidris canutus rufa stops for days or weeks in stopovers that it selects along its routes. Among them is the middle coast, in the extreme south of Brazil, where the Lagoa do Peixe National Park is also located. This place is characterized by having coastal ponds, wetland areas, extensive areas of dunes, stream channels and wide sandy beaches, an ideal environment for shorebirds. Here the results of two studies with this subspecies are presented. The monitoring of five individuals, started in April 2019, using PinPoint GPS Argos 75, from Lagoa do Peixe, with the aim of investigating migration routes and differences in migration strategies. The second, through censuses of flocks of Red Knots, between the years 2019 and 2020, with the objective of analyzing the habitat use during the migratory processes and if variables related to the environment would justify the pattern of the presence of birds in the habitat. In the first work, differences were found in routes, distances traveled, travel time, migration speed, stop times and connectivity. The birds migrated along the route of Central Brazil and the Atlantic Route. One of them performed a direct flight of 8,300 km, from Lagoa do Peixe to Delaware Bay - USA. Another stopped in Maranhão and a third accessed an unknown environment for the species, Baía Santa Rosa – Mouth of Amazonas River, Brazil. The fourth had a record on the Atlantic coast of Suriname. The migration speed ranged from 53 km / day to 1,230 km / day. Birds with better body condition covered greater distance in less time, above 900 km / day. This work highlights the existence of variation in migration strategies within the same population and demonstrates the importance of the connectivity of fundamental environments for the viability of the subspecies. In the second study, differences were found between the size and distance of the flocks. In the northward migration, the flocks are larger and maintain a greater distance between themselves. During the northward migration, the formation of two clusters with different environmental preferences was detected. A group at the southern end seems to be influenced by the size of the area of the ponds and wetlands and the flocks grouped at the northern end at the distance of ponds, wetlands and drainages channels were important to explain their presence. During the southward migration four clusters were identified, however the flocks were distributed more evenly throughout the area, and the most important variables for the flock groups were distance from the ponds and urban areas. The distance between the bands also played a complementary role. The variables distance from ponds, pond area, distance from drainages and urban areas were the variables that seem to better respond to the pattern of ordering the presence of flocks in the habitat. The distribution of the flocks is structured in areas that have a high similarity of the studied variables, denoting the influence of the environment in the places where the birds are present differently when migrating to their breeding or wintering areas. Habitat use studies are essential to identify preferred environments for the purple-breasted curlew that must be protected.
Keywords: Limícolas; Monitoramento; Rota; Ambiente; Área úmida; Lagoas; Shorebird; Monitoring; Flayways; Environment; Wetlands; Pond; ACCNPQ::Ciências Biológicas::Biologia Geral